Factors Affecting The Event of Anemia on Students - Hartati Hartati; Destriana Destriana; Marlina Marlina; Muslimin Muslimin (Journal Physical Education, Health and Recreation, 2020)
Anemia is a condition when the body lacks blood cells that contain hemoglobin to spread oxygen to all organs of the body. The impact of anemia for elementary school-age children is that it can cause problems of child growth and development. This study aims to determine the factors that influence anemia in SD Gedung Batin, Negara Inner sub-district, Way Kanan Regency, Lampung Province. This research uses descriptive analytic that is describing and explaining the factors that influence anemia status in 6th grade students at Batin Building, Negara Batin Subdistrict, Way Kanan Regency, Lampung Province. The population in this study were all elementary school students in Batin Building, Batin Negara District, Way Kanan Regency, Lampung Province, totaling 50 students. The sample in this study amounted to 17 students. Research instruments include questionnaires, data collected in the form of primary data and secondary data based on the results of research and data analysis with cross sectional. The analysis shows that the nutritional status based on body mass index BMI there are 5 normal nutrition students, 4 students are fat nutritional status and 8 students are classified as underweight nutritional status. According to normal weight 40%, and low 60%. normal height 53% and low 47%. The majority are 60% and 40% are minority. Parents' income is high as much as 47% and less 53%. 65% of junior high / high school education and 35% of senior high school / elementary / junior high school education. The implication in this research is finding factors that influence anemia, one of which is related to nutritional problems.